Transition of the adolescent transplant patient to adult care. Issue 5 (30th October 2013) - Fredericks, Emily M.; Lopez, M. James
<x xml:space="preserve">Abstract</x> Watch a video presentation of this article: http://onlinelibrary.wiley.com/journal/10.1002/(ISSN)2046‐2484/homepage/2‐5‐reading‐fredericks.htm Watch the interview with the author: http://onlinelibrary.wiley.com/journal/10.1002/(ISSN)2046‐2484/homepage/2‐5‐interview‐fredericks.htm Answer questions and earn CME: https://www.wileyhealthlearning.com/Activity/1976022/Activity.aspx